Motivasi Kerja Aparatur dalam Penyelenggaraan Pemerintahan di Kecamatan Belopa - Riska Amalia Armin; Muhammad Tamar; Andi Lukman Irwan (Departemen Ilmu Pemerintahan Fisip Unhas, 2009)
Abstract: This study aims to determine the efforts made in improving the motivation of personnel working in the district Belopa and know the factors that influence the motivation to work in the administration of government officials in the district Belopa. Type of study is a explanatif. form the study is a form of field research by using survey method. Data collection techniques performed using the technique literature study, observation, interviews, quisioner and search data online. Data were collected from various sources to obtain sufficient data. The results of this study indicate that efforts are made to improve the motivation of personnel working in governance at the district Belopa is